Development of a preliminary model for addressing naphthenic acid corrosion of ASTM A-335 P9 using an eco-enzyme green inhibitor on heavy-vacuum gas oil residue - Jaya, Kadek Ambara; Soedarsono, Johny; Pratesa, Yudha; Riastuti, Rini; Kaban, Agus (Eastern-European Journal of Enterprise Technologies, 2025)
ASTM A-335 P9 is widely employed within the piping infrastructure of the crude distillation unit for the conveyance of heavy vacuum gas oil (HVGO) crude residue before subsequent downstream processing, owing to its high mechanical properties. Due to elevated operating temperatures, the presence of sulfur, the material remains vulnerable to naphthenic acid corrosion, which can compromise its structural and operational integrity. This study examines the material’s response to the application of eco-enzyme as a green corrosion inhibitor (GCI) employing extensive several tests under naphthenic acid distillate which collected and processed from the heavy vacuum gas oil piping. optical emission spectroscopy (OES), ultraviolet-visible spectroscopy (UV-Vis), and Fourier rransform infra-red (FTIR) equipped with potentiodynamic polarization and electrochemical impedance spectroscopy (EIS) to dive into the corrosion resistance of EE inhibitor under the naphthenic acid extracts. Moreover, the scanning electronic microscopy and energy X-Ray dispersive (SEM-EDX) was utilized to reveal the surface morphology and the elemental identity of the retained inhibition mechanism. Based on the OES, the presence of Cr and Mo are highlighted with the composition of 9.135% and 0.894% which aligned with the 9Cr-1Mo material specification. The electronic transition of π-π* and n-π* transitions is in good agreement with the presence of aromatic -OH, C-H sp3, R-CHO, C=O, C-O and aromatic absorption at 525 nm, which correlates with peaks observed in FTIR spectra at 3200–3400, 2800–3000 cm-1. The high inhibition efficiency beyond 77% is correlated to the adsorption of the inhibitor that thermodynamically adheres to the Langmuir adsorption isotherm and applicable of model the HVGO system